(untitled) (Fiep Bulletin - online, 2013)
The aim of this study was to analyze the straight punch (Gyaku tsuki) in karate and evaluate if there are differences in three starting positions. The sample consisted of 10 (ten) karatekas black belt, with an age 22 (± 3.2) years, practice activity time 9.8 (± 3.1) years; The variables of this study were: reaction time (RT), wrist speed (Vp) and elbow angular velocity (?cot). The three starting positions were: a) hand over the belt (EFx) b) above the belt (AFX) below the belt (BFX). The punches were recorded with a high speed camera (240Hz). The assessment of reaction time was measured by the image and was the time between a visual stimulus and the first movement of the athlete. For elbow angular velocity and the wrist speed evaluation, markers were placed into skin in the shoulder joints, elbow and wrist. Data were analyzed using Peak Motus Software by Vicon ®. For statistical analysis was of variance (ANOVA) for repeated measures and between groups was performed to test post-hoc Bonferroni. The results showed no significant differences on values of TR, and Vp ?cot in three positions. The wrist speed values were similar to other studies. The values of reaction time showed lower values compared to other studies with martial arts and karate. The wrist velocities showed accordance with studies that evaluated the same technique. The elbow angular velocity showed values above studies of similar techniques (Choku Zuki). It can be concluded that in a combat situation does not exist a more advantageous position in which to become more efficient implementation of Gyaku tsuki. It seems that the high level of training, practice time and accuracy of the technical gesture makes the athletes use of compensatory actions to maintain the same performance. Further researches using other methods of biomechanics are necessary for a better motor actions understanding in Karate.